EFFICACY OF SAMUDRA LAVANA IN THE MANAGEMENT OF ANUNNAT NABHI WITH SPECIAL REFERENCE TO UMBILICAL GRANULOMA IN NEONATE - Gaikwad. Shilpa Tryambakrao; Raut Aparna Abhay (International Journal of Applied Ayurved Research, 2020)
Umbilical granuloma is the common umbilical condition in neonates, in Ashtanga hridya Acharya Vaghbhata explains two nabhirogas unnat nabhi and anunnat nabhi from which we can correlate anunnat nabhiroga with umbilical granuloma. Umbilical granuloma causes inflammation and persistent drainage .umbilical granuloma forms within first week after cord separation. If umbilical granuloma remains untreated it can ooze and cause persistent irritation for several days or months, umbilical granuloma look like moist and reddish tiny granular structure like ball .Size of umbilical granuloma ranges in between 1 mm to 10 mm. The most common treatment used to treat umbilical granuloma are chemical cauterization with silver nitrate or copper sulphate, electric cauterization, cryo cauterization, surgical excision, which causes irritation to patients and also it is very costly treatment and use of samudralavana treating umbilical granuloma is simple, can be performed by Non- medico person at home like mother, caretaker, and it is also cost effective & safe.